ПОДТВЕРЖДЕНИЕ ПАТОГЕНЕТИЧЕСКОЙ ГЕТЕРОГЕННОСТИ САХАРНОГО ДИАБЕТА У ДЕТЕЙ - Туркунова, Мария Евгеньевна; Дитковская, Лилия Викторовна; Башнина, Елена Борисовна; Тыртова, Людмила Викторовна; Суспицин, Евгений Николаевич; Берсенева, О С; Глотов, Олег Сергеевич; Серебрякова, Елена Андреевна; Глотов, Андрей Сергеевич; Иващенко, Татьяна Эдуардовна; Баранов, Владислав Сергеевич; Желенина, Людмила Александровна (Медицина: теория и практика, 2020)